Nuclear transcriptional activity of the tobacco plastid psbA promoter. - Cornelissen, M (1989)
The plastid psbA promoter of tobacco was used with the aim to construct plastid specific marker genes. Upon transfer to the tobacco nuclear genome the plastid promoter fragment appeared to specify a messenger RNA. Placed 5' to the bar or nptII coding sequences the level of expression is sufficient to obtain a selectable phenotype. The transcription start site in the nucleus is site specific and is located 4 nucleotides downstream relative to the start site used in plastids. Translational fusions of the psbA coding sequence with the nptII and bar coding sequences revealed that the psbA leader sequence and the psbA translation start codon, being the second ATG codon, are recognized by the plant cytoplasmic translation apparatus. A promoter cassette utilisable in both E. coli and tobacco, was obtained by placing the CaMV 35S enhancer 5' to the psbA promoter.